Digital Therapeutics: An Integral Component of Digital Innovation in Drug Development. Issue 1 (23rd February 2018) - Sverdlov, Oleksandr; van Dam, Joris; Hannesdottir, Kristin; Thornton‐Wells, Tricia
Abstract : Digital therapeutics represent a new treatment modality in which digital systems such as smartphone apps are used as regulatory‐approved, prescribed therapeutic interventions to treat medical conditions. In this article we provide a critical overview of the rationale for investing in such novel modalities, including the unmet medical needs addressed by digital therapeutics and the potential for reducing current costs of medical care. We also discuss emerging pathways to regulatory approval and how innovative business models are enabling further growth in the development of digital therapeutics. We conclude by providing some recent examples of digital therapeutics that have gained regulatory approval and highlight opportunities for the near future.